Consuming Anxieties: Mobility of Commodities across Religious Boundaries in Nineteenth-Century Morocco - Terem, Etty (Journal of the economic and social history of the Orient, 2017)
This article examines a fatwa written in the late nineteenth century by Jaʿfar b. Idrīs al-Kattānī, a distinguished Moroccan legal scholar. The issue that gave rise to the fatwa was the subject of heated debates among Moroccan Muslims at the time: the legality of using goods manufactured by non-Muslims. New historical conditions brought by Moroccan modernity eroded religious and communal boundaries between Muslims and non-Muslims and accentuated concerns about the integrity of Islam. Suspicion and anxiety of the population found expression in widespread rumors about impurities in products manufactured by non-Muslims. By analyzing al-Kattānī’s fatwa, this article aims to offer insights into the relationships between the ʿulamāʾ, Islamic tradition, and modernity.